ANALISIS YURIDIS PENENTUAN KEDUDUKAN SAKSI PELAKU SEBAGAI JUSTICE COLLABORATORS DALAM TINDAK PIDANA NARKOTIKA DI PENGADILAN NEGERI PEMATANG SIANTAR (Studi Putusan No: 231/Pid.Sus/2015/PN - Secsio Jimec Nainggolan; Syafruddin Kalo; Mahmud Mulyadi; Edy Yunara (USU LAW JOURNAL, 2017)
ABSTRACT Judge’s Ruling in Pematang Siantar District Court No. 231/Pid.Sus/2015/PN Pms decides lighter sentence than the prosecutor’s claim because the defendant is considered a justice collaborator. A defendant is considered to be a Justice Collaborator by Pematang Siantar District Court because he has helped as a witness and revealed the main narcotic dealer and the networks involved in the distribution of narcotics in Pematang Siantar and Simalungun District. The Judge considered that the defendant’s testimony as a justice collaborator of being cooperative. This case encourages a need to study the judge’s legal consideration in deciding the narcotic perpetrator as a justice collaborator in Pematang Siantar District Court. It needs to study whether the ruling which says that the narcotic perpetrator as a justice collaborator has been in accordance with the objective of the conviction. Keywords: Witness and Victim Protection Institution, Justice Collaborators, Narcotic Crime